Socio-Economic Analysis of Disaster Recovery Index in Donggala Regency - Tope, Patta; Ichwan, Mohamad; Jokolelono, Eko; Mangun, Nudiatulhuda; Anam, Haerul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The territory of Indonesia consists of an archipelago located in the pacific ring of fire. Under the waters of Indonesia, there is a collision of three large tectonic plates, namely the Eurasian Plate, Indo-Australian Plate, and the Pacific Plate which has and can cause volcanic explosions and earthquakes that are the deadliest in human history. The purpose of this research is to discuss about socio-economic analysis of disaster recovery index in Donggala Regency. Analysis of the problem in this study using the Indonesia Post-Disaster Recovery Index (Ina-PDRI). From the results of the study, it is found that disaster recovery index in Donggala Regency is 87.02 percent. This finding shows that socio-economic conditions in Donggala Regency are still better before natural disaster occurred by 12.98 percent compared to current conditions. This figure is obtained from the weighted average of disaster recovery index in the education sector which only reached 69.57 percent, disaster recovery index in the health sector which only reached 79.76 percent, and disaster recovery index in the economic sector which only reached 118.8 percent.